Implementasi Ayat-Ayat Hudud Dalam Tafsir Al-Azhar Sesuai Konteks Negara Indonesia - Satria tenun syahputra (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This article discuss about the implementation of Islamic law’s verses in al-Azhar exegesis to Indonesian context, being a largest moslem’s country in the world, Indonesia do not constitute the holy Quran as the primary sources of the country’s law, but rather to constitute UUD 1945 as a primary sources of the law and Pancasila as the country’s constitution, the status of HAMKA as a stateman who have started his career away before the establishment of the country and also as a well-known Islamic scholars, and the author of one of the famous Quranic exegesis in Indonesia Tafsir al-Azhar become the source of the scientific problem, how was the position of HAMKA as an islamic scholars to convey the islamic law firmly and explicitly, in the other hand, he must adjust his exegesis and implement it to Indonesian context which has their own product of law and constitution to demolish criminality, by using qualitative reasearch (Library Research) with the method of analisys-descriptive aproach focused to the al-Azhar exegesis found the efforts of HAMKA to integrate the islamic law with the country’s law and constitution, and is able to be implemented accordingly and simultenously, and also has a similarity, in addition there is also an opportuniy to constitute the islamic law to be the official law of the country by submitting the program to the government, based on the first pillar of Pancasila “ Believe in the One and Only God” which HAMKA stated as the fundamental power of Pancasila.